2010
DOI: 10.1115/1.4000789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Denoising on Acoustic Emission Signals

Abstract: The acoustic emission (AE) technology is growing in its applicability to bearing defect diagnosis. Several publications have shown its effectiveness for earlier detection of bearing defects than vibration analysis. In the latter instance, detection and monitoring of defects can be achieved through temporal statistical indicators, which can further be improved by application of denoising techniques. This paper investigates the application of temporal statistical indicators for AE detection of bearing defects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Thus, this condition can be used to evaluate potential defects and the service capabilities of the carbon fiber cable. Kurtosis is calculated as follows [17]:…”
Section: Cfrp Bridge Cablementioning
confidence: 99%
“…Thus, this condition can be used to evaluate potential defects and the service capabilities of the carbon fiber cable. Kurtosis is calculated as follows [17]:…”
Section: Cfrp Bridge Cablementioning
confidence: 99%
“…Liu et al [12] used the independent components analysis, Liao et al [13] employed wavelets analysis whilstŽvokelj et al [14] and Li et al [15] were interested in the empirical mode decomposition and Gabor transform, respectively, on AE signals. Chiementin et al [16] used time domain indicators RMS, Kurtosis, and proposes to improve the signal-to-noise ratio by applying denoising techniques (wavelet, spectral subtraction, sanc) on experimental acquired AE data. The use of traditional methods of vibration analysis for AE analysis offers yet further techniques for the diagnostician.…”
Section: Introductionmentioning
confidence: 99%
“…The WT has been used in many studies related to the Structural Health Monitoring (SHM) field [23][24][25][26][27][28]. Some other studies have reported on the use of the WT on AE signals for a denoising purpose [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%